Avaliação de diferentes grupos genéticos de bovinos de corte em cruzamentos com base no peso à desmama e ao sobreano - Santos, Alexandre Leseur dos (2010)
This study aimed to analyze the genetic groups of beef cattle in a multiracial population, through their progeny (half blood) derived from the mating of Angus, Hereford, Nellore and Senepol with Nellore arrays, and the progenies (tricross) of matrices F1 (Angus-Nellore) when mated or inseminated with bulls multiple Canchim, Simbrasil and Senepol. Data were available from BAMA farm, owned by JL Agriculture, located in the city of Juara in Mato Grosso - Brazil, through the Program for Genetic Improvement of Beef Cattle GENEPLUS - EMBRAPA - CNPGC, Campo Grande - MS. The mating scheme implemented is the use of bulls of the Angus, Hereford, Nellore and Senepol through artificial insemination in females Nellore. The products resulting from these matings males are destined for slaughter. The female half-blood Angus cattle are reserved for replacement of the squad playing with the use of multiple sires or artificial insemination of beef cattle breeds of Canchim, Simbrasil and Senepol. We used the observed values of weaning weight, yearling weight and corrected to 240 and 450 days. The ages of the animals weighing ranging from 150 to 399, and 340 to 647 days to weaning and yearling, respectively. The data from this study were collected at the beginning of 2002 until the end of 2008. We evaluated the difference between bulls within each breed group (Angus, Hereford, Nellore and Senepol) formed by the race of the father, and later the differences between genetic groups (1/2Angus+1/2Nellore, 1/2Hereford+1/2Nellore, Nellore, 1/2Canchim+¼Angus+¼Nellore, 1/2Simbrasil+¼Angus+¼Nellore e 1/2Senepol+¼Angus+¼Nellore). To carry out the assessments we used models that considered the effects of contemporary groups, formed the basis of month of birth and sex as covariates and age of the animal body weight, age of calving, linear and quadratic. For the analysis between all groups were used 12046 observations of weight and weaning weight of 7224 yearling, with totals of 122 and 88 contemporary groups for the traits weight at weaning and yearling respectively. The effect of contemporary groups, age of dam and age of the animal weighed for weaning weight and yearling were significant (P<0.0001), verifying the importance of including these effects in multiracial evaluation of beef cattle. The use of linear adjustment for the effect of age of the animal at weaning has been shown as a good approximation. However for yearling was not sufficient to remove any effect of age. Based on the results also concluded that the use of crossbreeding bulls of the Angus, Hereford and Senepol with Nellore females may be an alternative to improve the weight at weaning and yearling cattle when compared to Nellore. Crossbred animals performed better than to Nellore, weaning and yearling. The animals through blood were similar to tricross at weaning and yearling higher. Among the animals tricross, no difference was found between the genetic groups evaluated.